ZrO2-Modified LiMn2O4 Thin-Film Cathodes Prepared by Pulsed Laser Deposition - Shin, Dong Wook; Choi, Ji-Won; Ahn, Jae-Pyoung; Choi, Won-Kook; Cho, Yong Soo; Yoon, Seok-Jin (ELECTROCHEMICAL SOC INC, 2010)
The study on the influences of ZrO2 addition in LiMn2O4 thin films as cathodes was driven by the need to improve the physical and electrochemical performances of thin-film lithium batteries. The films of xZrO(2)-LiMn2O4 at x=0.025 possessed a high capacity retention of >82% at 4C after 130 cycles, compared to 68% at x=0, due to the formation of amorphous ZrO2 on the grain boundary and surface out of the LiMn2O4 matrix via the pulsed laser deposition. The ZrO2 modification decreased the charge-transfer resistance (R-ct) and unwanted phase transition of the LiMn2O4 cathode film.
Keywords: LITHIUM BATTERIES; ELECTRODE